2015
DOI: 10.1109/tmtt.2015.2495141
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of Microstrip Gap Waveguides and Their Transitions to Rectangular Waveguide, for Millimeter-Wave Applications

Abstract: The paper describes the design methodology, experimental validation and practical considerations of two millimeterwave wideband vertical transitions from two gap waveguide versions (inverted microstrip gap waveguide, and microstrip packaged by using gap waveguide) to standard WR-15 rectangular waveguide. The experimental results show S11 smaller than -10 dB over relative bandwidths larger than 25% and 26.6% when Rogers RO3003 and RO4003 materials are used respectively. The vertical transition from standard mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Since the wave propagates mainly in the air and surface waves do not exist, the width of the lines in gap waveguides become wider than typical microstrip and SIW. A V-band transition between inverted microstrip gap waveguide and rectangular waveguide was presented and validated with both simulations and measurements in [7]. Measurement results confirmed that the overall loss in inverted microstrip gap waveguide is lower than in conventional microstrip and SIW.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Since the wave propagates mainly in the air and surface waves do not exist, the width of the lines in gap waveguides become wider than typical microstrip and SIW. A V-band transition between inverted microstrip gap waveguide and rectangular waveguide was presented and validated with both simulations and measurements in [7]. Measurement results confirmed that the overall loss in inverted microstrip gap waveguide is lower than in conventional microstrip and SIW.…”
Section: Introductionmentioning
confidence: 60%
“…First, the bed of nails composing the inverted gap geometry must be designed. For this purpose, the same transitions as in [7] have been reused and these dimensions are shown in Fig. 1(a) and Table I.…”
Section: Inverted Microstrip Gap Waveguide End-coupled Filter Designmentioning
confidence: 99%
“…However, new versions of gap waveguide transitions are required as the frequency increases. Several suitable transitions working at 60 GHz have been already studied and experimentally validated [12], [13]. In addition, some investigations on transitions between a ridge gap waveguide and standard rectangular waveguides at 0.3 THz have been also initiated.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, during 2015 and 2016, from Chalmers, Algaba has presented several advanced transitions [860]- [862]. In [860], a complete work, including design methodology, experimental validation and practical considerations is presented.…”
Section: (D)mentioning
confidence: 99%
“…In [860], a complete work, including design methodology, experimental validation and practical considerations is presented. Two transitions are designed: SSGW to WR-15, and microstrip packaged with GW technology (later explained in section 8.2.2.7) to WR-15.…”
Section: (D)mentioning
confidence: 99%